Design and Implementation a Management Information System Extracurricular WebBased (Case Study: SMAN 1 Sampang) - Achmad Hamdan; I Made Irawan; M. Zainal Arifin (Journal of Disruptive Learning Innovation (JODLI), 2019)
This research aims to design and implement a Management Information System Extracurricular Web-Based in SMA Negeri 1 Sampang to be able to further improve the performance of the school in extracurricular management. SMA Negeri 1 Sampang is a leading public school in the town of Sampang. However extracurricular school management system is still not supported by good information technology facilities. And so we need an information system as an efficiency improvement of school performance in extracurricular management. This research using research design development. The this development goal is to develop a extracurricular management information system web-based as a means to improve the performance of the school in order to support the extracurricular management skills to further develop the student maximum and can also support the academic achievement of students. This development using Waterfall model. The conclusion of this research is that the extracurricular management information system is declared to be feasible and valid to be used because the percentage generated is quite high, namely the average usability aspect of 89.54 percent and the functionality aspect of 99.99 percent.Keyword: Information System, Management, Extracurricular